Knowledge, Attitude and Practice of Dots Providers Under RNTCP in Ujjain, Madhya Pradesh - Mayank Jain; Swarupa V Chakole; Amit S Pawaiya; Satish C Mehta (Medsci Publications, 2012)
Background: India has the highest burden of TB worldwide. Every year approx 1.8 million people developed tuberculosis and 0.37 million die. Aim: To study knowledge, attitude and practice of DOTS Providers under RNTCP in Ujjain, Madhya Pradesh. Material and Method: All DOTS providers of Ujjain city were interviewed by using a questionnaire, which included questions regarding their knowledge about TB, their attitude and actually how they provide the DOTS. Result: 56.9% of DOTS provider has good knowledge of TB. It was significantly higher in men (72.4%; P=0.04), respondent aged< 30 (79.5%) (P< 0.05) and DOTS provider who are in health services (P=0.016). 100% identified cough for more than two weeks as the symptom of TB. Correct knowledge of case definition of default, relapse and failure was shown by 45.5%, 34.3%, 20.6 % respectively. 80.4 % provide DOTS during home visit. Conclusion: Knowledge of DOTS providers is not satisfactory about Tuberculosis. Knowledge is good in those who have higher qualification and are in health related services. Attitude and Practice of only 36.3 % of DOTS provider is very good.